PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Kadek Diah Candra Dewi; I Gede Riana (Distribusi - Journal of Management and Business, 2019)
OCB is a positive behavior that will have an impact on the organization as a whole so it is important for organizations to encourage the emergence of OCB behavior for each employee the purpose of this study is to analyze the effect of work motivation, organizational commitment and job satisfaction on organizational citizenship behavior PNS at the Badung Regency DPRD Secretariat. The number of samples in this study were 87 civil servants using the probability sampling method which is a saturated sample technique. Data collection in this study was carried out through questionnaires and interviews. The analysis technique used is multiple linear regression analysis. The results of this study indicate that work motivation, organizational commitment and job satisfaction have a significant influence on OCB.